THE ADJACENCY PAIRS IN “TALK ASIA” INTERVIEW BETWEEN INDONESIA PRESIDENT SUSILO BAMBANG YUDHOYONO WITH STEVENS FROM CNN - Ai Siti Nurhasanah; Ajeng Febrina Yolanda; Trisnendri Syahrizal (PROJECT (Professional Journal of English Education), 2019)
This research focus on adjacency pairs in “Talk Asia” Interview between President SBY with Stevens from CNN. This research had aimed to find out what types of AP and preference structure used in“Talk Asia” Interview between Indonesian President SBY with Stevens from CNN. Qualitative method was used to analyze this research. The researchers take the interview from CNN  between Indonesia president SBY with Stevens as the instrument for research. The result found that was four question-answer, two assessment-agreement/disagreement, one request-acceptance/refusal, one farewell-farewell, it means that the dominant type of AP in “Talk Asia” Interview between Indonesia President SBY with Stevens from CNN is question-answer. For preference structure there are two preferred and one dispreferred.